Pemanfaatan Apotek Hidup di Perumahan - Dedy Affandy; Rian Vebrianto; Mery Berlian; Aldi Prasetia; Miftah Audhiha (Anotero Lembaga Scientific Pekanbaru, 2021)
The implementation of the real work lecture of this devotional live pharmacy program aims to indetify the types of medicinal plants in addition to herbal medicine in an effort to improve health degrees in the community, to know how to use it, the benefits and uses of some medicinal plants in housing, as raw materials for herbal medicine and as an alternative to overcoming chemical drugs that are expensive. The medicinal plants found can be used as traditional medicine, from minor ailments to degenerative diseases well as fitness enhancer. This is important because it knows the medicinal plants of a live pharmacy. This devotion is carried out by Participatory Action Research (PAR) carried out using qualitative descriptive methods. Then the sampling of plants by the Proportional Random Sampling by 15%. The live pharmacy program was implemented on August 4-August 10, 2021 in Perumahan Cendrawasih RW.04 Kelurahan Air Putih Tuah Madani involving 30 devotional participants. Data is taken using a questionnaire instrument (kuistioner) to find out the success / impression of the implementation of the devotion program. From the results of analysts it is known that the program of planting a live pharmacy in the value of success and devotion participants strongly agree / agree with this devotion program